2005
DOI: 10.1139/e05-004
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Chart of the evolution of the Trans-Hudson Orogen — Manitoba–Saskatchewan segment

Abstract: A correlation chart showing the evolution of the Manitoba–Saskatchewan segment of the Paleoproterozoic Trans-Hudson Orogen (THO) has been constructed based on available geochronological and isotopic data. Geological, petrological, geochemical, and structural data have also been incorporated into the correlation chart to provide finer detail and to allow comparison of specific tectonic events. The chart also emphasizes that the bounding Archean cratons (Superior, Hearne, Sask) have been significantly affected b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Many of the concepts adopted for outputs from the StratDB system are based on correlation charts produced by previous compilers e.g. Hartzer et al (1998), Wardle et al (2002) and Ansdell et al (2005), all of which were produced using standard commercial graphics packages.…”
Section: Origin Of the Database Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of the concepts adopted for outputs from the StratDB system are based on correlation charts produced by previous compilers e.g. Hartzer et al (1998), Wardle et al (2002) and Ansdell et al (2005), all of which were produced using standard commercial graphics packages.…”
Section: Origin Of the Database Systemsmentioning
confidence: 99%
“…The principal legend for the space-time charts is illustrated in Figure 7. This legend is based on the one used for previous compilations of Canadian Palaeoproterozoic terranes (Wardle et al, 2002;Ansdell et al, 2005), but with data shown as a matrix derived from two properties: rock Figure 11 illustrates the lithostratigraphy and metamorphism for the interval from ~2300 Ma to 1800 Ma. Here, we illustrate that it is possible to compile and present different correlation schemes, for instance that of the South Africa Committee for Stratigraphy (SACS) (as most recently summarised by Eriksson et al (2006) and Moen (2006)) and more recent work based on dating of detrital zircons in sediments of the Kimberley domain.…”
Section: Time-space Correlation Chartsmentioning
confidence: 99%
“…General soil physical and chemical properties are presented in Table 2. The soils are ultimately derived from granitic bedrock of the Glennie domain (Â1.85 billion yr old; Ansdell et al 2005), which crops out at the top of the watershed. Mixed woods grow on sandy loam soils that developed as Eluviated Dystric Brunisols (Soil Classification Working Group 1998).…”
Section: Site Descriptionmentioning
confidence: 99%